(untitled) (Palimpsesto, 2025)
This study examines the tensions in the care practices of people with disabilities in their families and the complexities that arise at the intersection of disability and various axes of inequality. Using the theory of Situated Knowledge, we conducted a collaborative study of co-constructed Life Narratives about the experiences of seven disability activists in Chile. A thematic analysis was conducted to reconstruct the tensions of family actions from an intersectional intracategorical perspective (McCall, 2005), which emphasizes various axes of oppression within the category of “disability,” such as socioeconomic status, gender, and sexuality. Three dimensions emerge regarding the relationship between families and disability: families are held socially responsible, tensions between overprotection and autonomy, and ableism in the pursuit of independence.